The Effect of Ownership Structure and Investor Protection on Firm Value: Analyst Following as Moderating Variable - Susilawati, Desi; Rakhman, Fuad (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
The research related to the association between structure ownership and the firm value is a discussion about corporate governance which is still has contradictory conclusion and mixed result. It indicates open question that needs empirical evidence. The influence of concentrated ownership on firm value still brought conflict of interest so the role of analyst following can be stated as an alternative of corporate governance mechanism (Lang et al., 2004). The objectives of this research are to examine the interaction effect between concentrated ownership and analyst following, and the effect of investor protection toward firm value in five Asian companies. Asia is chosen because it has unique characteristic, in term of corporates ownership structure which is more concentrated on families and board of governance is weak (Choi, 2003). The data is consisting of 7.100 firm year observations obtained from Bloomberg and OSIRIS database for the period 2011-2013 in five Asian Countries, i.e. China, South Korea,Â Malaysia, Taiwan, and Thailand. Multiple Regression analysis is used to test hypotheses. The results show that concentrated ownership is positively affects the firm value. However, there is no empirical evidence that the interaction of concentrated ownership and analyst following positively affect the firm value. As hypothesized, this research also shows that investor protection has negative impact on firmâ€™s value.